Nursing of a patient with infertility caused by chronic pelvic inflammatory disease treated with the Chinese herbal medicine ointment rubbing therapy (中药膏摩治疗1例慢性盆腔炎所致不孕症的护理体会) - TENG Yue (滕悦); LU Ying (卢英); WANG Xuejing (王雪静); YANG Man (杨曼) (中西医结合护理)
This paper summarized nursing measures for a patient with infertility caused by chronic pelvic inflammatory disease treated with the Chinese herbal medicine ointment rubbing therapy. Based on the Traditional Chinese Medicine syndrome differentiation and nursing assessment, the Chinese herbal medicine rubbing therapy and comprehensive nursing interventions such as dietary care, emotional care and life support were carried out to relieve the pain and anxiety, and improve the absorption of pelvic inflammatory effusion. (本文总结1例中药膏摩治疗慢性盆腔炎所导致不孕患者的护理经验, 通过辨证分型和护理评估制定护理方案, 采取中药膏摩治疗, 同时做好饮食调护、情志护理和生活指导等护理措施, 减轻患者疼痛、缓解焦虑、促进盆腔积液吸收, 满足了患者的生育需求。)